A novel active current co‐efficient extraction‐based control for grid‐tied solar photovoltaic system. Issue 12 (22nd March 2021) - Jalan, Subham Kumar; Babu, B. Chitti; Patel, Nirav; Kumar, Ajay; Gupta, Nitin
Abstract: In this paper, a novel active current co‐efficient extraction (ACCE)‐based control method is presented for a three‐phase grid‐interfaced voltage source inverter (VSI). Since the VSI performance largely depends on the reference current generation method, it is of significance to identify the active current co‐efficient of the load current contaminated with harmonics, as it is a key governing factor that decides the shape of the compensating current. The proposed ACCE structure functions with minimal mathematical operators like product, sum, and integrators and thereby identifies the fundamental current with computational effectiveness. Besides, in comparison to existing prevalent state‐of‐the‐art methods, the proposed ACCE structure is devoid of any low‐pass filter and zero‐crossing detector, and hence serves the following two distinctive purposes: (i) Ensures minimum steady‐state oscillations and (ii) exhibits improved dynamic performance under disturbances in the grid and load. The proposed structure effectively confronts the various power quality challenges while injecting the active power into the utility grid. Further, the incremental‐conductance‐based maximum power point tracking algorithm is equipped to extract the maximum possible power from the photovoltaic array. Finally, the effectiveness of the proposed ACCE structure has been investigated through MATLAB/Simulink software studies followed by dSPACE‐1104‐based experimental setup.